Influence of family support on leisure activities and mental health in times of health crisis - García-Gallegos, Janeth Berenice; Delgado-Herrada, Maritza; Morquecho-Sánchez, Raquel; Leale, Ignazio; Zamarripa, Jorge (Frontiers in Psychology, 2026)
Physical activity is an essential pillar for promoting health and comprehensive well-being throughout life. During the COVID-19 pandemic, lockdown and social restriction measures significantly transformed family routines and lifestyles, leading to an increase in sedentary behavior and negative effects on mental health. This article aims to analyze the influence of family support on mental health, mediated by physical activity and sedentary behaviors during the COVID-19 lockdown. A total of 1,345 Mexican adults (68.1% women) participated, responding to validated instruments: the Social Support for Physical Activity Scale, the Godin-Shephard Leisure-Time Physical Activity Questionnaire, the Youth Leisure-Time Sedentary Behavior Questionnaire, and the Positive and Negative Affect Schedule (PANAS). Structural equation modeling analyses showed a satisfactory model fit (χ2/df = 6.71, CFI = 0.931, RMSEA = 0.060). Family support was positively associated with active leisure and, more weakly, with passive leisure. Furthermore, active leisure was related to greater positive affect, while passive leisure was associated with psychological distress. These results highlight the protective role of the family in promoting physical activity and emotional regulation in lockdown contexts. It is recommended to design family intervention programs that integrate educational, affective, and behavioral components to foster active lifestyles and strengthen resilience for future health crises.